2017
DOI: 10.1097/inf.0000000000001668
|View full text |Cite
|
Sign up to set email alerts
|

First Cases of Severe Flaccid Paralysis Associated With Enterovirus D68 Infection in Spain, 2015–2016

Abstract: Enterovirus D68 was known to be the cause of mild to severe respiratory infections, but in the last few years, it has also been associated with myelitis and paralysis. This report describes the first Enterovirus D68 detections in acute flaccid paralysis cases occurring between December 2015 and March 2016 in Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 10 publications
4
23
1
5
Order By: Relevance
“…Regarding the clinical manifestations, most of EV-D68 detected were associated with LRTI, highlighting its possible association with severe respiratory illnesses [20]. Similarly to other European cases [21,22], only one case, a 2-year-old girl, developed AFP in February 2016 [15]. EV-D68 usually causes more severe disease in patients with asthma or reactive airway, as previously reported [23,24], but herein only one case was reported.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Regarding the clinical manifestations, most of EV-D68 detected were associated with LRTI, highlighting its possible association with severe respiratory illnesses [20]. Similarly to other European cases [21,22], only one case, a 2-year-old girl, developed AFP in February 2016 [15]. EV-D68 usually causes more severe disease in patients with asthma or reactive airway, as previously reported [23,24], but herein only one case was reported.…”
Section: Discussionsupporting
confidence: 72%
“…Before the neurologic complications, 5/25 (20%) of cases began with EV-A71-related HFMD, 3/25 (12%) with herpangina (2 EV-A71 and 1 CV-A10) and 6/25 (24%) with exanthema (5 EV-A71 and 1 EV-C109). Only one patient developed permanent neurologic disabilities due to cardiorespiratory failure and hypoxic-ischemic encephalopathy, in addition to one AFP case, but associated with EV-D68 infection [15].…”
Section: Neurological Complicationsmentioning
confidence: 95%
“…In addition to respiratory infections, EV-D68 has been associated with neurological complications in recent years [11,[17][18][19][20][21]. During our study-period, this virus was identified in 16 children and one adult with neurological symptoms.…”
Section: Discussionmentioning
confidence: 75%
“…Since 2014, an increasing number of EV-D68 outbreaks associated with severe respiratory diseases, mainly in children, have been occurring in different countries, first in the US and Canada, followed by Europe and Asia. Concurrently, clusters of cases with neurological complications such as myelitis or acute flaccid paralysis were reported in the same geographical areas [9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation